TINGKAT KESADARAN ASN TERHADAP PERAN GENDER DI SEKRETARIAT WILAYAH KOTA MANADO - Rompas, Frensy Chisty Mariane; Kawung, Evelin J. R.; Goni, Shirley Y. V. I. (HOLISTIK, Journal Of Social and Culture, 2020)
Gender equality and justice is one of the goals of the eight global goals of the world countries committed in the Millennium Development Goals (MDGs). Equality and Justice of Gender (KKG) has become a very important issue and has become the commitment of the nations in the world including Indonesia so that the entire country become bound and must carry out the commitments. Therefore women empowerment programs have become the agenda of the nation and require the support of all parties. Therefore women empowerment programs have become the agenda of the nation and require the support of all parties. The regularity of women reflects the inequality between men and women in Indonesia, this can be seen from the picture of the condition of women in Indonesia. One of the role of gender is the consciousness of the State Civil Apparatus (ASN) which has not been so maximal in carrying out the work so that in determining the positions of certain women's position is still minimal compared to the males, the strong patriarchal culture certainly weakens the position of women, this is due to ASN awareness of gender conscious programs have not been implemented in theirTherefore, the gender role for ASN is to improve public services as closely as possible without gender discriminate. Gender equality in human resource management, especially for ASN, is the system and recruitment of ASN candidates need to be made changes.Keywords: gender, women, state civil apparatus